Assessing the Role of State and Local Public Health in Outreach and Enrollment for Expanded Coverage Seven Case Studies from Local and State Health Departments - Williams, Malcolm V. (RAND Corporation, 2016)
This report summarizes seven case studies to highlight innovative models and best practices from seven case studies that leverage local health department (LHD) efforts in Patient Protection and Affordable Care Act outreach and enrollment to facilitate knowledge transfer to other geographic regions. Also, they provide guidance and insight into the current and future role of LHDs, as states continue to enroll residents in health insurance coverage.